Deciphering Southern Thailand's violence organization and insurgent practices of BRN-Coordinate - Helbardt, Sascha (ISEAS Yusof Ishak Institute, 2015)
Scholars have given questions about the perpetrators of nameless violence in Southern Thailand little consideration, leaving the motives that drive Barisan Revolusi Nasional (BRN) heavily cloaked in secrecy and speculation.This book offers a rare glimpse behind the veil that shrouds BRN-Coordinate. Using exclusive access to and detailed interviews with BRN-Coordinate members, this book analyses the communicative dimension of the insurgency. It depicts the hidden channels and organized violence that drive the regions enduring rebellion as well as BRN's dichotomous existence between silence and communication.